Walter Crane : de l’album considéré comme un des Beaux-Arts - Isabelle Guillaume (Cahiers Victoriens et Edouardiens)
With his picture books sold in tens of thousands of copies by publishers for young people, with his wallpapers intended for the nursery, Walter Crane created a work representative of the place taken by the child in Victorian society. He imagined these works for a specific editorial sector, for a restricted territory within the family and social space. His books for young people and their engravings could therefore appear as a separate production from the watercolors and paintings that this symbolist painter exhibited in London galleries and presented at various World Fairs, for example in Paris in 1878 and in Chicago in 1893. They could also be considered inferior to these because of their medium, their recipient and the specific social function assigned to them. The economic and educational place of cultural objects for children in Victorian society was not synonymous with literary or artistic consecration. The hierarchy which places the productions for the youth in situation of less aesthetic value overlaps that which distinguishes the fine arts from the arts known as "minor". Picture books would thus join the ceramics, textiles and mosaics designed by Walter Crane. Precisely, in his theoretical essays as in his practice, he worked in favor of a new configuration of the artistic field alongside William Morris. Leader of the second generation of Pre-Raphaelites and initiator of the Arts and Crafts movement, Morris advocated the abolition of the hierarchy between artistic practices in favor of the emergence of a homogeneous class of creators producing objects and artworks. As shown by his toy books and three square books published by Routledge, the former between 1865 and 1876, the latter between 1877 and 1887, it was by being located in the artistically and socially compartmentalized field of children’s publishing that Walter Crane best succeeded in creating and representing works that were apparently diverse but, in reality, conceived from the complementary angles of experimentation, totality and mise en abyme work.